MENEMBUS BATAS LAHIRIAH PERSPEKTIF AL-GHAZALI: Refleksi bagi Dunia Pendidikan - Salahuddin, Salahuddin (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2015)
Abstract: This study aimed to describe the view of al-Ghazali about how to view and interpret the text. The focus of the study was directed to the nature behind the term, examples of Sufi interpretation, and pedagogical reflection. The writer examined the text contained in Ihya Ulum al-Din and Misykat book. The results showed that al-Ghazali recommended to not just focus and stop at the term, but it also should explore the deepest meaning without ignoring the meaning of the term as a benchmark and a starting point. Sufi esoteric interpretations of the water in the QS 13/17 is ma'rifat, valleys mean the human heart, and spring called the Qur'an primordial. In the perspective of education, educators need to teach students not only the textual meanings of a text, but also the truth (philosophy) behind it. Abstrak: Kajian ini bertujuan untuk memaparkan pandangan al-Ghazali tentang cara melihat dan memaknai teks. Fokus kajian diarahkan pada hakikat di balik istilah, contoh tafsir sufistik, dan diakhiri dengan refleksi paedagogis. Penulis menelaah teks yang terdapat dalam kitab Ihya Ulum al-Din dan kitab Misykat. Hasil kajian menunjukkan bahwa al-Ghazali menganjurkan untuk tidak hanya terpaku dan berhenti pada istilah, tetapi lebih dari itu harus menyelami makna terdalamnya tanpa mengabaikan makna istilah sebagai patokan dan titik berangkat. Tafsiran sufistik esoterik tentang air dalam QS 13/17 ialah ma’rifat, lembah-lembah berarti kalbu manusia, dan mata air disebut dengan Al-qur’an primordial. Dalam pers-pektif pendidikan, seorang pendidik perlu mengajarkan kepada peserta didik bu-kan hanya makna lahiriah dari suatu teks, melainkan juga hakikat di balik makna lahiriah tersebut.